2005
DOI: 10.1029/2004jd005603
|View full text |Cite
|
Sign up to set email alerts
|

Coastal water source of short‐lived halocarbons in New England

Abstract: [1] Short-lived halocarbon tracers were used to investigate marine influences on air quality in a coastal region of New England. Atmospheric measurements made at the University of New Hampshire's Observing Station at Thompson Farm (TF) in Durham, New Hampshire, indicate that relatively large amounts of halocarbons are emitted from local estuarine and coastal oceanic regions. Bromine-containing halocarbons of interest in this work include bromoform (CHBr 3 ) and dibromomethane (CH 2 Br 2 ). The mean mixing rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
98
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 67 publications
10
98
2
Order By: Relevance
“…A three gas chromatograph system equipped with two flame ionization detectors (FID), two electron capture detectors (ECD), and a mass spectrometer (MS) was used for analysis of each 1500 cc (STP) sample aliquot. The PLOT-FID, OV-1701-ECD, and OV-624-MS column-detector combinations have remained the same throughout 2004-2008 (see Sive et al (2005) and Zhou et al (2005Zhou et al ( , 2006Zhou et al ( , 2008 for additional information). In 2006, the FID channel used for C 4 -C 10 NMHC analysis was changed from a DB-1 column (60 m×0.32 mm I.D., 1 µm film thickness) to a VF-1ms column (60 m×0.32 mm I.D., 1 µm film thickness).…”
Section: Daily Canister Sample Collection and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A three gas chromatograph system equipped with two flame ionization detectors (FID), two electron capture detectors (ECD), and a mass spectrometer (MS) was used for analysis of each 1500 cc (STP) sample aliquot. The PLOT-FID, OV-1701-ECD, and OV-624-MS column-detector combinations have remained the same throughout 2004-2008 (see Sive et al (2005) and Zhou et al (2005Zhou et al ( , 2006Zhou et al ( , 2008 for additional information). In 2006, the FID channel used for C 4 -C 10 NMHC analysis was changed from a DB-1 column (60 m×0.32 mm I.D., 1 µm film thickness) to a VF-1ms column (60 m×0.32 mm I.D., 1 µm film thickness).…”
Section: Daily Canister Sample Collection and Analysismentioning
confidence: 99%
“…We followed a simple box model approach which has been effectively used in previous studies to calculate emission and removal rates of trace gases in this region (i.e., Talbot et al, 2005;Zhou et al, 2005;Sive et al, 2007;White et al, 2008;Russo et al, 2010). This method uses measurements made on nights with low wind speeds and when a stable inversion layer has developed because under these conditions, the exchange of air between the nocturnal boundary layer (NBL) and the residual layer above is limited (e.g., Hastie et al, 1993;Gusten et al, 1998;Talbot et al, 2005).…”
Section: Emission Rates Estimated From Observations At Tfmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that this area is influenced by marine, vegetative, and anthropogenic sources of nonmethane hydrocarbons (NMHCs) and halocarbons (Sive et al, 2007;Varner et al, 2008;White et al, 2008White et al, , 2009Zhou et al, 2005Zhou et al, , 2008 and is strongly impacted by boundary layer dynamics (Mao and Talbot, 2004a;. In this work, we characterize the seasonal and diurnal variability, sources, and sinks of C 1 -C 5 alkyl nitrates at an inland site (Thompson Farm) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…TF is surrounded by a mixed forest and is located ∼ 20 km inland from the Gulf of Maine, 5 km northwest of the Great Bay estuary, and ∼ 100 km north of Boston, MA. Samples were analyzed onsite by an in situ automated gas chromatography (GC) system equipped with two flame ionization detectors (FID) for detecting NMHCs and two electron capture detectors (ECD) for measuring halocarbons and alkyl nitrates (described in detail by Zhou et al, 2005. The measurement precision for each of the hydrocarbons, halocarbons, and alkyl nitrates ranged from 0.3-15%.…”
Section: Introductionmentioning
confidence: 99%